The Influence of Consumption, Production, Price, and Exchange Rate on Indonesia's Rice Imports - Mohamad Rapi Safi'i (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This research investigates how annual rice consumption, domestic rice output, cultivated land area, rice prices, and the exchange rate impact Indonesia's rice import volume from 2009 to 2024. Despite statistical data indicating that national rice production is sufficient to satisfy domestic demand (BPS, 2023), Indonesia continues to import substantial quantities of rice. This contradiction suggests the presence of broader macroeconomic factors influencing import trends. A quantitative inferential method was used in this study, employing multiple linear regression in a log-log model to estimate elasticities. The analysis utilized secondary data from BPS and was conducted using EViews software. To validate the model, several classical assumption tests were conducted, including the Jarque-Bera test for normality (p = 0.126), multicollinearity assessment via the Variance Inflation Factor (all VIF values below 10), the ARCH test for heteroskedasticity (p = 0.5435), and the Durbin-Watson test for autocorrelation (DW = 1.84). The analysis showed that rice prices significantly and positively influence import volume, whereas the exchange rate has a significant negative impact. In contrast, consumption, production, and harvested land area were found to have no statistically meaningful effects. These outcomes suggest that rice importation is more strongly influenced by market conditions and monetary factors than by basic supply and demand imbalances. Therefore, enhancing distribution networks and strengthening the role of institutions like Bulog is critical to decreasing reliance on imports.